2014
DOI: 10.1039/c4sm00316k
|View full text |Cite
|
Sign up to set email alerts
|

Exposing nanobubble-like objects to a degassed environment

Abstract: The primary attribute of interest of surface nanobubbles is their unusual stability and a number of theories trying to explain this have been put forward. Interestingly, the dissolution of nanobubbles is a topic that did not receive a lot of attention yet. In this work we applied two different experimental procedures which should cause gaseous nanobubbles to completely dissolve. In our experiments we nucleated nanobubble-like objects by putting a drop of water on HOPG using a plastic syringe and disposable nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
111
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(114 citation statements)
references
References 58 publications
3
111
0
Order By: Relevance
“…By contrast, after exchanging the ethanol again with water, the surface was found to be covered with round structures that correspond to previous work reporting on surface nanobubbles (Figure 1c). Even though no disposable syringes or needles, which are known to introduce polysiloxane based 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 contamination into the liquid cell and onto the sample surface, 21,43 However, unlike following this indirect degassing strategy, which cannot differentiate easily a volatile water-insoluble organic liquid from gas, the work discussed here exploits FLIM, which identifies the gas-filled surface nanobubbles via the characteristic emission component lifetime of the reporter dye Rh6G, when it is partitioned to the gas-water interface. We have verified in independent measurements that water surface tension demonstrates some decrease in the presence of Rh6G.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, after exchanging the ethanol again with water, the surface was found to be covered with round structures that correspond to previous work reporting on surface nanobubbles (Figure 1c). Even though no disposable syringes or needles, which are known to introduce polysiloxane based 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 contamination into the liquid cell and onto the sample surface, 21,43 However, unlike following this indirect degassing strategy, which cannot differentiate easily a volatile water-insoluble organic liquid from gas, the work discussed here exploits FLIM, which identifies the gas-filled surface nanobubbles via the characteristic emission component lifetime of the reporter dye Rh6G, when it is partitioned to the gas-water interface. We have verified in independent measurements that water surface tension demonstrates some decrease in the presence of Rh6G.…”
Section: Resultsmentioning
confidence: 99%
“…20 How can one directly distinguish between oil droplets and air bubbles in situ? Optical microscopy is very versatile and allows visualization of many dyes that would absorb into oils.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The authors explained such a behaviour by assuming the presence of some surface-active impurity, which contaminated the liquid-air interface. A recent experimental study on nanobubble-like object generation 38 reported the unexpected presence of PDMS contaminant in sterile disposable needles, which made clear how difficult is to control the presence of impurity within a sample even when working with standard microfluidic cleaning procedures.…”
Section: Discussionmentioning
confidence: 99%